Evaluation of functional state of muscular system in children with diabetes mellitus - Pashkova, O. Ye.; Chudova, N. I.; Пашкова, Олена Єгорівна; Чудова, Наталя Ігорівна; Пашкова, Е. Е.; Чудова, Н. И. (Запорізький державний медичний університет, 2020)
Aim. To evaluate the functional condition of skeletal muscles in children with type 1 diabetes (T1D), according to the duration of disease based on studying static and dynamic physical endurance. Materials and methods. 76 children with T1D from 11 to 17 years old were examined. The first group included 20 kids with the duration of diabetes less than 1 year. The second group – 27 patients with T1D from 1 to 5 years. The third group – 29 kids with T1D over 5 years. The group of control included 16 conventionally healthy children. Static muscular endurance with evaluation of total static muscular endurance (TSME) and dynamic muscular endurance with evaluation of wrist strength index (WSI) were evaluated. The index of muscle quality (IMQ) was evaluated too. Results. The greater duration of T1D was accompanied by the redistribution of percentage ratio of body components. The TSME was decreasing alomg with increase of T1D duration. Reverse correlation between glycated hemoglobin and TSME (r = -0.50; P < 0.05) was shown. The dynamic endurance revealed the progressing decrease of WSI before and after the physical exertion in children with T1D in comparison with the control group. The revealed peculiarities of functional condition of muscles were connected with TSME (r = +0.43, P < 0.05) and IMQ (r = +0.52, P < 0.05). Conclusions. Functional condition of skeletal muscles in children with T1D is characterized by decrease of static and dynamic muscular endurance. The first signs of changes are observed over the first year of disease and progress as the duration of a disease increases and leads to decrease of mucle mass and diabetic myopathy developing. The major factor contributing the worsening of functional condition of muscles is insufficient glycemic control. Мета роботи – оцінити функціональний стан скелетної мускулатури в дітей із цукровим діабетом 1 типу (ЦД1) залежно від тривалості захворювання на основі вивчення статичної та динамічної фізичної витривалості. Матеріали та методи. Під спостереженням перебували 76 дітей віком від 11 до 17 років, які хворі на ЦД1. У 1 групу ввійшли 20 дітей із тривалістю ЦД1 до 1 року, у 2 групу – 27 дітей із перебігом захворювання від 1 до 5 років, у 3 групу – 29 дітей із тривалістю ЦД1 понад 5 років. Групу контролю становили 16 умовно здорових дітей. Для оцінювання функціонального стану м’язової системи визначали статичну й динамічну витривалості скелетних м’язів з обчисленням сумарної статичної витривалості (ССВ) та індексу кистьової сили (ІКС). Також визначали показник якості м’язів (ПЯМ). Результати. Збільшення «стажу» ЦД1 супроводжувалося перерозподілом компонентного складу тіла. Зі збільшенням тривалості ЦД1 погіршувався показник ССВ. Виявили зворотний кореляційний зв’язок між глікованим гемоглобіном і ССВ (r = -0,50; р < 0,05). Під час дослідження динамічної витривалості виявили зниження ІКС до та після навантаження в дітей із ЦД1 порівняно з групою контролю, що прогресувало в динаміці захворювання. Виявлені особливості функціонального стану м’язів пов’язані з показником ССВ (r = +0,43, р < 0,05), а також із ПЯМ (r = +0,52, р < 0,05). Висновки. Функціональний стан скелетної мускулатури в дітей із ЦД1 характеризувався зниженням статичної та динамічної м’язової витривалості. Перші ознаки змін спостерігали вже на першому році захворювання, вони прогресують зі збільшенням тривалості ЦД1 і призводять до зниження м’язової маси, розвитку діабетичної міопатії. Основний фактор ризику, що зумовлює погіршення функціонального стану скелетних м’язів, – недостатній глікемічний контроль. Цель работы – оценить функциональное состояние скелетной мускулатуры у детей с сахарным диабетом 1 типа (СД1) в зависимости от длительности заболевания на основании изучения статической и динамической физической выносливости. Материалы и методы. Под наблюдением находились 76 детей в возрасте от 11 до 17 лет, больных СД1. В 1 группу вошли 20 детей с продолжительностью СД1 до 1 года, 2 группу составили 27 детей с длительностью заболевания от 1 до 5 лет, 3 группа состояла из 29 детей с длительностью СД1 более 5 лет. Группу контроля составили 16 условно здоровых детей. Для оценки функционального состояния мышечной системы определяли статическую и динамическую выносливость скелетных мышц с вычислением суммарной статической выносливости (ССВ) и индекса кистевой силы (ИКС). Также оценивали показатель качества мышц (ПКМ). Результаты. Установлено, что увеличение «стажа» СД1 сопровождалось перераспределением компонентного состава тела. С увеличением продолжительности СД1 ухудшался показатель ССВ. Установлена обратная корреляционная связь между гликированным гемоглобином и ССВ (r = -0,50; р < 0,05). При исследовании динамической выносливости отмечено снижение ИКС до и после нагрузки у детей с СД1 в сравнении с группой контроля, которое прогрессировало в динамике заболевания. Особенности функционального состояния мышц связаны с показателем ССВ (r = +0,43, р < 0,05), а также с ПКМ (r = +0,52, р < 0,05). Выводы. Функциональное состояние скелетной мускулатуры у детей с СД1 характеризуется снижением статической и динамической мышечной выносливости. Первые признаки изменений наблюдали уже на первом году заболевания, они прогрессируют с увеличением длительности СД1, приводят к снижению мышечной массы и развитию диабетической миопатии. Основной фактор риска, который способствует ухудшению функционального состояния скелетных мышц, – недостаточный гликемический контроль.
Оцінювання функціонального стану м’язової системи в дітей, які хворі на цукровий діабет
Оценка функционального состояния мышечной системы у детей, больных сахарным диабетом
Пашкова О. Є. - ORCID ID: 0000-0002-3935-5103; Чудова Н. І. - ORCID ID: 0000-0001-5641-1843.
Keywords: type 1 diabetes; children; muscular strength; diabetic myopathy; цукровий діабет 1 типу; діти; витривалість м’язів; діабетична міопатія; сахарный диабет 1 типа; дети; выносливость мышц; миопатия